2009
DOI: 10.1148/radiol.2511080128
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma: Value of Diffusion-weighted MR Imaging for Nodal Staging

Abstract: DW imaging performed with ADC(b0-1000) values had higher accuracy than turbo spin-echo MR imaging in nodal staging, providing added value in the detection of subcentimeter nodal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
233
4
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(251 citation statements)
references
References 41 publications
10
233
4
4
Order By: Relevance
“…Interpretation of DW or dynamic enhanced MRI scans of the head and neck region is not straightforward, making the use of quantitative or semiquantitative measurements for target volume delineation absolutely necessary. However, this necessity is also one of the strengths of the technique, since a straightforward cutoff value would allow simple and reliable differentiation, potentially eliminating both intra-and interobserver variability (15). Also, DW or dynamic enhanced MRI scans have a nonnegligible nonaffine distortion, making fusion with planning-CT images difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interpretation of DW or dynamic enhanced MRI scans of the head and neck region is not straightforward, making the use of quantitative or semiquantitative measurements for target volume delineation absolutely necessary. However, this necessity is also one of the strengths of the technique, since a straightforward cutoff value would allow simple and reliable differentiation, potentially eliminating both intra-and interobserver variability (15). Also, DW or dynamic enhanced MRI scans have a nonnegligible nonaffine distortion, making fusion with planning-CT images difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI protocol has previously been detailed (14,15). The examinations were performed on a 1.5-T scanner (Magnetom Sonata Vision; Siemens) using a combination of a standard head coil and a 2-channel phased-array neck coil.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that the ADCs of various causes of lymphadenopathy are significantly different from each other (36)(37)(38) and that the ADCs of metastatic and nonmetastatic lymph nodes may also show significant differences (39)(40)(41), the ADCs of normal lymph nodes and those of different nodal pathologies or conditions overlap. Furthermore, because of the susceptibility of echoplanar imaging-based DWI to image distortions, its insufficient spatial resolution, and partialvolume-averaging effects, inter-and intraobserver reproducibility in ADC measurements may be limited, causing unreliable evaluation of normal-sized lymph nodes (42).…”
Section: Limitationsmentioning
confidence: 98%
“…For lymph node staging ADC values have found to be the strongest independent predictor for the presence of nodal metastases [49] and significantly improve the detection of small metastatic lymph nodes (4 -9 mm), which remain false-negative based on pure size and morphology criteria [50]. For the evaluation of treatment response it has been shown that two-week intra-treatment ADCs are predictors of outcome, as a lower increase in the percentage change of the mean ADC, higher skewness, and higher kurtosis are significantly more likely to show local failure than local control [51].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%